Association Between Preeclampsia Onset During Pregnancy and the Risk of Postpartum Preeclampsia - Ivon Diah Wittiarika; Hesty Katarina Tahu; Budi Prasetyo; Andriyanti; Ningrum, Astika Gita (Universitas Muhammadiyah Sidoarjo, 2026)
Preeclampsia is recognized as a significant cause of maternal mortality in Indonesia as well as globally. Approximately 40% of maternal deaths occur during the postpartum period. Preeclampsia during pregnancy can continue into the postpartum period. The onset of preeclampsia has an impact on maternal outcomes. Studies on postpartum preeclampsia have not been widely conducted. The objective of this study is to investigate the relationship between preeclampsia onset and the occurrence of postpartum preeclampsia. The study design is an observational analytical study using a case-control approach (retrospective). The population in this study consisted of all medical records of postpartum mothers who gave birth and were treated at Regional General Hospital, East Nusa Tenggara, the period from January to December 2023. The sample consisted of 42 case groups and 42 control groups selected using simple random sampling. The analysis used was the Chi-Square test. There was no significant association between the onset of preeclampsia and the occurrence of postpartum preeclampsia based on the Chi-square test (p = 0.178) with a significance level of p < 0.05. However, patients who experienced early-onset preeclampsia demonstrated a greater tendency toward postpartum preeclampsia. Preeclampsia during pregnancy increases the incidence of postpartum preeclampsia, with pathophysiology occurring in endothelial dysfunction, systemic inflammation, and failure of spiral artery remodeling. The impact of this process does not always stop after the placenta is delivered. Some clinical evidence shows that markers in the body can still cause postpartum clinical manifestations.